Sleep and development familial and socio-cultural considerations - El-Sheikh, Mona. (New York ; Oxford : Oxford University Press, 2011)
Sleep problems of American children have become a matter of national concern. This text integrates knowledge and approaches from numerous disciplines to focus on the sleep and development of children across adjustment and cognitive domains.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Sleep disorders; Children -- Sleep; Sleep deprivation; Families